2021
DOI: 10.1101/2021.11.12.21266291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of infants secondary to in utero exposure to maternal SARS-CoV-2 infection: A national prospective study in Kuwait

Abstract: BackgroundAn increasing proportion of women are being infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during pregnancy. Intrauterine viral infections induce an increase in the levels of proinflammatory cytokines, which inhibit the proliferation of neuronal precursor cells and stimulate oligodendrocyte cell death, leading to abnormal neurodevelopment. Whether a maternal cytokine storm can affect neonatal brain development is unclear. The objective of the present study is to assess neu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Early signals of adverse neurodevelopmental outcomes at 3-6 months, 1 year, and 1.5 years in infants and children exposed to SARS-CoV-2 in utero, and/or born during the COVID-19 pandemic are emerging [37][38][39][40][41]. A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early signals of adverse neurodevelopmental outcomes at 3-6 months, 1 year, and 1.5 years in infants and children exposed to SARS-CoV-2 in utero, and/or born during the COVID-19 pandemic are emerging [37][38][39][40][41]. A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
“…A longitudinal cohort study of 57 infants with prenatal exposure to SARS-CoV-2 in China identified deficits in the social-emotional domain of neurodevelopmental testing at 3 months of age [40]. A preliminary report of 298 infants born to women with SARS-CoV-2 infection during pregnancy found evidence of developmental delay in 10% of infants at 12 months of age, although neither study included a noninfected comparator group [41]. Another preliminary report of over 7000 infants born during the COVID-19 pandemic to both SARS-CoV-2 infected and noninfected mothers identified an association between maternal SARS-CoV-2 exposure and a neurodevelopmental diagnosis at 12 months [25].…”
Section: Early Evidence Of Adverse Neurodevelopmental Outcomes In Chi...mentioning
confidence: 99%
“…Fortunately, maternal-fetal vertical transmission of SARS-CoV-2 is rare, although the impact of maternal infection on fetal and postnatal neurodevelopment is still poorly understood. 12 Recently, a few cohort studies 13 , 14 , 15 , 16 on this clinically important issue have been published with controversial results. Shuffrey et al, 15 as one of the largest cohorts, assessed 255 infants born during the pandemic, and exposure to maternal SARS-CoV-2 infection was not associated with differences in neurodevelopmental screening scores at age 6 months, regardless of infection timing or severity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies demonstrated early signals (e.g. at 3-6 months, 12, and 18 months) of neurodevelopmental risk in offspring exposed to SARS-CoV-2 in utero 29,30(p19),31 , although those studies were limited by the absence of a contemporaneous non-infected control group. A preliminary report in a subset of the present cohort, including a non-infected contemporary control group, suggested that SARS-CoV-2 was associated with increased risk for neurodevelopmental diagnosis at 12 months of age, 19 but did not yet have sufficient neurodevelopmental diagnoses to examine the impact of fetal sex, as we have now been able to examine in this substantially larger cohort.…”
Section: Discussionmentioning
confidence: 99%